PENGARUH JABATAN ORGANISASI, BUDAYA ORGANISASI, DAN KONFLIK PERAN AUDITOR INTERNAL TERHADAP KEPUASAN KERJA INTERNAL AUDITOR (Studi pada Badan Urusan Logistik di Indonesia) - Abdul Rohman (Jurnal Telaah dan Riset Akuntansi, 2009)
The main purpose of the study is to test the effects of position in organization, organization culture, and role conflict of internal auditor toward job satisfaction of internal auditor. This Studi is done on Bulog (Badan Urusan Logistik) in Indonesia.The primary data are collected from internal auditors who work in government department that is Bulog. The data are collected by interviewing directly 71 respondents and mailing survey for 180 people. So, there are 251 respondents in this research. From 251 respondents, the data can be collected only from 148 respondents, in detail, 93 respondents (51,67%) from mailed survey and the rest 55 respondents (77,46%) from interview technique. After being reexamined by using multivariate SEM technique that is supported by AMOS and SPSS 10 programs, the data can be processed only from 103 respondents.The result of this research shows that the job satisfaction of internal auditor will be influenced if position of internal auditor in organization is high. The hypothesis stating that the organization culture has positive effect toward job satisfaction of internal auditor is denied. The role conflict of internal auditor gives negative effect toward job satisfaction of internal auditor.             Key words        :Position in organization, organization culture, role conflict, job satisfaction, internal auditor.